Belief, Faith, and Hope: On the Rationality of Long-Term Commitment. Issue 517 (13th June 2020) - Jackson, Elizabeth
Abstract: I examine three attitudes: belief, faith, and hope. I argue that all three attitudes play the same role in rationalizing action. First, I explain two models of rational action—the decision-theory model and the belief-desire model. Both models entail there are two components of rational action: an epistemic component and a conative component. Then, using this framework, I show how belief, faith, and hope that p can all make it rational to accept, or act as if, p. I conclude by showing how my picture can explain how action-oriented commitments can be rational over time, both in the face of counterevidence and in the face of waning affections.